Analytic Hierarchy Process Dalam Pembobotan Untuk Pengaturan Jadwal Dosen - Menur Wahyu Pangestika; Alda Cendekia Siregar (CYBERNETICS, 2018)
Scheduling is one of the important things in teaching and learning process. The Analytical Hierarchy Process (AHP) method is a system analysis method that can be used to connect unstructured situation into a spesific part that used to make an effective decisions. The application of AHP based on the decomposition of objectives, evaluates values through pairwise comparisons in stages and able to choose the best alternative from some alternatives. The purpose of this study is to prove whether the AHP method can be used to determine scoring for the election of lecturer schedules and to knowing the result of AHP’s scoring The data in this study are: criteria of the subjects, lecturers, SKS, lecturer status, space, time to determine the score and alternative, namely in the form of even semester teachers. As for producing departmental recommendations, input is needed in the form of score resulting from the AHP calculation and calculating the space that shows the floor, day and course. This study uses comparative data and the same alternative from previous studies,that is scheduling data for the Even Semester of Mechanical Engineering Study Department that certain on scheduling for regular lectures. The final results of this study include several names that can be used for scheduling first. Judging from the previous research using the DS / AHP method, 17 lecturers got the order from 29 lecturers, but in this study, the whole can be sorted.